Developing a Practice‐Based Research Network by Integrating Quality Improvement: Challenges and Ingredients for Success - Baldwin, Laura‐Mae (Blackwell Publishing Inc, 2012)
Improving patient outcomes in community‐based settings is the goal of both the Clinical Translational Science Award program and practice‐based quality improvement (QI) programs. Given this common goal, integrating QI and outcomes research is a promising strategy for developing, implementing, and evaluating clinical interventions. This article describes the challenges and strengths illuminated by the conduct of a combined research/QI study in a nascent practice‐based research network. Challenges include research's exclusion of clinic patients who might benefit from the intervention; QI programs’ less uniform approach to intervention implementation; and the need for both academic and clinically relevant products and publications. A major strength is the increased likelihood of both engaging clinical practices in research and developing successful clinical interventions. Required elements for success include identification of enthusiastic clinical research “champions,” involvement of researchers with clinical experience, and adequate funding to support both research and clinical resources and dissemination. Combined Ql/research projects in the practice‐based research environment have the potential to improve and shorten the cycle from good idea to improved clinical outcomes in real‐world settings. Clin Trans Sci 2012; Volume 5: 351–355